Safety of Eicosapentaenoic Acid in Cancer Treatment: Effect on Cancer Cells and Chemotherapy in Vitro. (21st April 2021) - Aktaş, Safiye; Ercetin, Pınar; Altun, Zekiye; Kantar, Mehmet; Olgun, Nur
Abstract: Eicosapentaenoic acid (EPA) is a long-chain polyunsaturated fatty acid that has been used to treat cachectic cancer. However, its efficacy and safety with regard to cancer cells remain unclear. The present study comprised an In Vitro investigation of the effects of EPA on cancers. The effects of 0.01–300 μg/mL of EPA on the proliferation and death of cells after 24, 48, and 72 h were explored. The study included cell lines representing neuroblastoma (Kelly, SH-SY5Y, C1300); acute lymphoblastic leukemia (ALL); Burkitt's lymphoma; acute myeloid leukemia (AML); adult cancer cell lines of the pancreas, colon, and prostate; and a fibroblast cell line. EPA caused 4.4%–7% proliferation of fibroblasts, but did not protect them from the toxic effect of cisplatin. It did not induce proliferation in the neuroblastoma cells, and did not reduce the cytotoxic effect of cisplatin. EPA also did not cause proliferation in ALL, Burkitt's lymphoma, and AML cells, and did not alter the cytotoxic effects of L-asparaginase, cyclophosphamide, and cytosine arabinoside, respectively. Our results were similar in the adult cancer cell lines. EPA is safe because it has no effects on the proliferation of cancer cells or on chemotherapy In Vitro.